Equality and Diversity in the Dutch Welfare State - Douwe van Houten (Social Work & Society, 2007)
Under the Constitution, the equality principle is very important in the Netherlands. This article argues that there is little evidence for equal citizenship in the Netherlands. There is anti-discrimination legislation in the Netherlands, but it is not very robust. The core argument in this article is that the equality principle must be supplemented by the diversity principle. Diversity is multi-dimensional and can refer to religion, philosophy of life, political persuasion, race (ethnicity), gender, nationality, sexual orientation, age, disability and chronic illness. In this paper multi-culturalism and disability are taken into account and we make a comparison of the social position of disabled people and people from ethnic minorities. Policies on diversity are needed to arrive at diverse citizenship in a varied society. This implies that a distinction has to be made between political citizenship and cultural citizenship. The former has to do with equality, and the latter with diversity.